Eksplorasi Kebutuhan Produk Halal di Kalangan Konsumen Muslim Kalimantan Selatan: Studi Empiris tentang Persepsi dan Preferensi Label Halal - Lisda Aisyah; Muhaimin Muhaimin; Zulpa Makiah (Islamic Economics and Business Faculty of UIN Antasari, 2026)
Indonesia's Halal Product Assurance Law (Law No. 33/2014), now implemented under Government Regulation No. 42/2024, mandates halal certification nationwide, yet little is known about how Muslim consumers in non-Javanese, Muslim-majority regions perceive and prioritize halal labeling in daily consumption. This qualitative descriptive field study used semi-structured interviews with 130 purposively sampled Muslim informants across all 13 regencies/cities of South Kalimantan (97.06% Muslim, Banjar-majority), combined with observation and documentation (triangulation) and analyzed via the Miles and Huberman model; response-category frequencies are reported descriptively, not inferentially. Most informants treated halal labeling as decisive in consumption decisions (87%), extending beyond packaged goods into informal food stalls, canteens, and street vendors (63%), even in non-Muslim-majority localities. A smaller, consistent minority (13-25%) instead relied on personal trust in known Muslim sellers, indicating formal certification and relational trust operate as complements rather than substitutes. In this Muslim-majority setting, halal labeling functions less as a minority-market device for accessing halal meat and more as a locally embedded instrument of trust, safety, and religious identity that consumers expect applied inclusively across formal and informal sectors, with implications for BPJPH's certification-prioritization strategy and halal literacy programming..